1967
DOI: 10.1136/gut.8.4.408
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of tryptic activity in intestinal juice as a diagnostic test of pancreatic disease.

Abstract: EDITORIAL COMMENT The concentration of trypsin in duodenal contents following a Lundh test meal containing 6 % of fat, 5 % protein, and 15 % carbohydrate, has been used as an index of exocrine pancreatic function. Low concentrations of trypsin are found in pancreatic disease, such as chronic pancreatitis and cancer of the pancreas. The test is particularly useful in the diagnosis of pancreatic steatorrhoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2

Year Published

1968
1968
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 8 publications
4
37
2
Order By: Relevance
“…Analysis of the results showed that chronic or recurrent pancreatitis and carcinoma of the head of the pancreas were associated with extremely depressed peak trypsin levels (more than 3 sd below the normal mean in six out of eight and three out of three patients respectively). These findings support the original conclusions of Lundh (1962) and of subsequent workers (Cook et al, 1967;McCarthy and Brown, 1969).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Analysis of the results showed that chronic or recurrent pancreatitis and carcinoma of the head of the pancreas were associated with extremely depressed peak trypsin levels (more than 3 sd below the normal mean in six out of eight and three out of three patients respectively). These findings support the original conclusions of Lundh (1962) and of subsequent workers (Cook et al, 1967;McCarthy and Brown, 1969).…”
Section: Discussionsupporting
confidence: 91%
“…The technique of pancreatic stimulation and sampling using a standard test meal was essentially that described by Cook et al (1967). The patients were studied after fasting overnight.…”
Section: Clinical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of values found in the test is shown in Table 4. On the whole there is good discrimination between normal and diseased glands (Cook et al, 1967;McCarthy and Brown, 1969 (Marks and Bank, 1963). Another such test is the estimation of faecal chymotrypsin and this can be performed on out-patients by an analysis of two stool samples per patient (Amman et al, 1968).…”
Section: Pancreatic Function Testsmentioning
confidence: 99%
“…Tryptic activity, whose lower limit of normal is 9.6micro-equiv. min./2 h., is measured using a synthetic substrate and an auto-titrator (Cook, Lennard-Jones, Sherif, and Wiggins, 1967).…”
Section: Investigation Ofpancreatic Functionmentioning
confidence: 99%